1979
DOI: 10.2307/3280290
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Five Strains of Mice to Babesia microti of Human Origin

Abstract: One outbred (CF1) and four inbred (BALB/c, C57, CBA and C3H) strains of mice were tested for susceptibility to Babesia microti of human origin. Of these, intact C3H mice developed higher parasitemia than all other intact mice, while BALB/c mice developed the highest parasitemia among splenectomized mice. Susceptibility was not related to H-2 haplotype in any obvious way. Because C3H and BALB/c mice developed relatively high initial peak parasitemias, the parasite was serially passaged in both of these mouse st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
34
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 8 publications
2
34
0
Order By: Relevance
“…Mice infected with B. microti produced transient high levels of parasitemia, but subsequently recovered from acute infection within 24 to 38 days. A self-limiting course was observed in all strains, whether splenectomized or intact [10].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Mice infected with B. microti produced transient high levels of parasitemia, but subsequently recovered from acute infection within 24 to 38 days. A self-limiting course was observed in all strains, whether splenectomized or intact [10].…”
Section: Introductionmentioning
confidence: 91%
“…microti can infect many species of animals [9] and different strains of mice with different susceptibility to infection [10]. Previous studies compared the susceptibility of one outbred (CF1) and four inbred (BALB/c, C57, CBA, and C3H) strains of mice with human-origin B. microti.…”
Section: Introductionmentioning
confidence: 99%
“…strain WA1, and susceptible mouse models. [23][24][25][26][27][28][29] Aguilar-Delfin and others reported a sex-related influence on resistance to acute Babesia sp. strain WA1 infection in C57BL/6 mice, with males being more resistant than females.…”
mentioning
confidence: 99%
“…However, the hamsters are not suitable to control infection as reservoir rodent hosts showing spontaneous remission with low parasitemia of less than 0.5% infected erythrocytes in the chronic and convalescent stages [8]. Mice are susceptible for mouse-adapted B. microti strains, but not so for the primary infection with the strains maintained in Syrian hamsters [22]. In this study, we confirmed that Chinese hamsters were susceptible to the infection with B. microti and would be useful for the infective examination with the patasite.…”
mentioning
confidence: 99%
“…Syrian hamsters (Mesocricetus auratus) have high susceptibility to B. microti infection and are used to isolate and maintain the parasite in laboratories [4,16,21], but the hamsters are not suitable rodent reservoir hosts to control the infection with the parasite, because they show spontaneous remission with low parasitemia [8]. Several species of mice are more commonly used for experimental infections with the parasite, but the mouse-adapted parasites are essential for experimental infections [22]. The rodents are as small as mice and susceptible to B. microti as well as Syrian hamsters, so they will be useful for infection experiments with the parasite.…”
mentioning
confidence: 99%